Assessment of levels of specific synthetic food colours And preservatives in selected commonly consumed Food products in Chennai - FAMITHA SIDDIQUE,; NORA VIGASINI, (International Journal of Pharma and Bio Sciences, 2016)
Food products sold in local markets in India often contain synthetic food colours and preservatives at levels higher than the amounts prescribed by the food safety laws and standards. In this study, samples of food products such as fruit drink, Indian sweets and savouries, papads, vegetable and fruit products, chicken masalas and tea leaves sold in unorganized petty shops were analyzed for the presence and levels of specific synthetic food preservatives and colours such as sorbic acid, benzoic acid, carmosine, tartrazine, brilliant blue, Ponceau 4R and sunset yellow. Samples tested were found to contain benzoic Acid in excess which is a potent carcinogen. Excess synthetic colours were found to have been added in four out of five tea samples tested, three out of five samples of savouries, three out of five samples of papads, three out of five samples of Chicken masalas and two out of five samples of vegetable and fruit products. Thus regular consumption of foods containing synthetic additives pose serious health risks to consumers.